Being a real nurse: A secondary qualitative analysis of how public health nurses rework their work identities. Issue 4 (25th June 2020) - Drevdahl, Denise J.; Canales, Mary K.
Abstract: Many Western nations are emphasizing the importance of population health across health care delivery organizations and education systems. Despite significant momentum to integrate population health into nursing practice, a parallel effort to examine how these efforts impact practicing nurses' views of their professional role and work identity has not occurred. This secondary qualitative analysis, employing an abductive approach, explored processes public health nurses use in creating and maintaining their work identity through three organizing themes: narrative self‐identity, mandated identity, and identity as struggle. The analysis was based on interview data collected from 30 US public health nurses residing in 17 states. 'Being a real nurse' describes public health nurses' efforts to balance a contradictory work identity where at times they are expected to focus on populations and at other times, on individuals. The identity work revealed through this study should be further explicated and specific strategies developed for stabilizing a work identity for public health nurses, as well as for any nurse charged with a population health role.